MOLECULAR MODELING OF CATIONIC PORPHYRINS AS LIGAD OF RADIOPHARMACEUTICAL KIT - Ni Made Pitri Susanti; Rahmana E. Kartasasmita; Amir Musadad; Daryono H. Tjahjono (Jurnal Kimia (Journal of Chemistry), 2011)
Cationic porphyrins and their interactions with DNA have become an important concern due to its role as a photosensitizer in photodynamic therapy for cancer treatment. However, this therapy technique has the disadvantage, i.e. its inability to document photographically the fluorescence observed endoscopically. The present research aims to observe the change in molecular level of cationic porphyrins which labeled by radionuclides emitting ? particle and ? radiation. Molecular models of 5,10,15,20-tetrakis-[3.4-bis (carboxymetylenoxy) imidazoliumyl] porphyrin (T3,4BCImP), 5,10,15,20-tetrakis-[3,4-bis (carboxymetylenoxy) pirazoliumyl] porphyrin (T3,4BCPzP) and its complexes which labeled by Tc and Re radionuclides were optimized and calulated by density functional theory methods (DFT). Atomic charges were calculated with natural population analysis/NPA method. The calculation result showed that Tc-T3,4BCPzP has the highest photosensitivity and the strongest affinity to DNA. Carboxylate groups of meso-subtituent of porhyrins lead to label cationic porphyrins by Tc and Re as radiopharmaceutical ligand candidates .